Organizational-Economic Model of Management of Infrastructure of Small Business Support in the Service Sphere - RUDENKO, Lyudmila G.; ZAITSEVA, Natalia A.; LARIONOVA, Anna A.; MELNICHENKO, Lesya N.; KOMISSAROVA, Irina P. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The relevance of the problem, stated in the article, is conditioned by the gaining importance of the service sphere, it becomes the foundation for the production, but its contribution to the Russian economy, significantly falls behind the developed countries, that dictates the need to analyze the development of small business in the field of services and identify the problems and search for new and effective forms of organization of small business infrastructural support (ISSB). The main purpose of the article is to develop the organizational and economic model of management of infrastructure of small business support in the service sector. Developed organizational and economic model of management of ISSB in the service sector is based on the systematic approach, including eight obligatory aspects: element, target, structural, functional, resource, integration, communication and historical. The structure of introduced organizational and economic model of management of infrastructure of small business support includes three levels of management entities, subject to control, support mechanisms and their implementation, assessment indicators of infrastructure support. The model aims to integrate the organizational, legal, financial, informational and consulting SB support mechanisms and should be implemented above all at the regional level, by reference to territorial and local interests. Article materials may serve for the practical usage to the specialists and executives of federal and local authorities.